2021
DOI: 10.3389/fimmu.2021.617163
|View full text |Cite
|
Sign up to set email alerts
|

The Changes of Leukocytes in Brain and Blood After Intracerebral Hemorrhage

Abstract: Preclinical and clinical research has demonstrated that inflammation is a critical factor regulating intracerebral hemorrhage (ICH)-induced brain injury. Growing evidence suggests that myeloid cells and lymphocytes have an effect on the pathophysiological processes associated with ICH, such as inflammation, immune responses, perihematomal edema formation, blood–brain barrier (BBB) integrity, and cell death. However, the underlying mechanisms remain largely unknown. We aimed to explore the role immune cells pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Second, initial peripheral immune activation is observed approximately six hours after experimentally induced ICH. In our study, the median time interval between stroke onset and first assessment of NLR (admission NLR) was 4.3 h (25-75 IQR: 2.2-11.1 h), and other authors have reported median ICH onset to NLR assessment time intervals of ≈6 h [9,19]. Thus, calculation of this ratio at the moment of hospital admission might be too early to identify any peripheral immune changes induced by the ICH and might reflect the effects of the neural-immune crosstalk only on its initial upslope, thereby limiting its value as a predictor of in-hospital mortality and short-term outcome.…”
Section: Discussionsupporting
confidence: 58%
“…Second, initial peripheral immune activation is observed approximately six hours after experimentally induced ICH. In our study, the median time interval between stroke onset and first assessment of NLR (admission NLR) was 4.3 h (25-75 IQR: 2.2-11.1 h), and other authors have reported median ICH onset to NLR assessment time intervals of ≈6 h [9,19]. Thus, calculation of this ratio at the moment of hospital admission might be too early to identify any peripheral immune changes induced by the ICH and might reflect the effects of the neural-immune crosstalk only on its initial upslope, thereby limiting its value as a predictor of in-hospital mortality and short-term outcome.…”
Section: Discussionsupporting
confidence: 58%
“…13 Stroke-associated immune suppression might inhibit the overwhelming brain inflammation but increase the risk of systemic infection because of the disruption of immune defense. 14,15 The current study adds that immune modulators, such as fingolimod or immunoglobulin, should be administered early in ICH, as long-term use may exacerbate immune suppression. 16,17 Lymphopenia is increasingly recognized as a consequence of acute illness and may predispose to infections.…”
Section: Discussionmentioning
confidence: 96%
“…Another point of contention is the possibility that these related molecules may be derived from other immune cells described abobe. In our ICH mouse model, the macrophage responses would begin within a few hours after onset, and then the lymphocyte response begins on around Day 3 and later [ 64 ]. As the therapeutic window of our study was Days 1–3 after the onset of ICH, we speculated that macrophages would be the main source of these molecules during this period.…”
Section: Discussionmentioning
confidence: 99%